Safety-Specific Leadership, Goal Orientation, and Near-Miss Recognition: The Cross-Level Moderating Effects of Safety Climate - Lu, Hongxu; Wu, Ting; Shao, Yan; Liu, Yanbin; Wang, Xiaoxuan (Frontiers in Psychology, 2019)
Near-miss recognition is an increasingly important area of research in safety management. Drawing on self-determination theory, we ask whether and how safety-specific transformational leadership and safety-specific active transactional leadership promote near-miss recognition. We also explore the boundary condition by focusing on the moderating role of safety climate. We analyze time-lagged data from 370 participants, and find that safety-specific transformational leadership enhances employees’ near-miss recognition (by enhancing their learning goal orientation), and that safety-specific active transactional leadership also positively influences employees’ near-miss recognition (by stimulating their performance goal orientation). In addition, we show that safety climate strengthens the relationship between safety-specific transactional leadership and employees’ performance goal orientation, but does not affect the relationship between safety-specific transformational leadership and employees’ learning goal orientation. We discuss the implications and limitations of the research.